2020
DOI: 10.1002/pc.25766
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of flax fiber‐reinforced composites at different relative humidities: Experimental, geometric, and displacement potential function approaches

Abstract: Due to the good mechanical properties, flax fiber-reinforced epoxy composites are being widely used as a green alternative to glass fiber composites. However, plant fibers absorb moisture from the environment, being in a higher moisture uptake as the relative humidity (RH) increases. This absorbed moisture deteriorates the mechanical properties of the composites. In this study, geometric and displacement potential function (DPF) approaches are used to predict the mechanical properties of flax fiber-reinforced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
(35 reference statements)
2
17
0
Order By: Relevance
“…Hybrid composites showed 40% higher mechanical properties than individual fiber composites. Moudood et al [26] studied the mechanical properties of flax fiber reinforced composites at different relative humidifies: experimental, geometric, and displacement potential function approaches. The experimental results indicated that improved tensile strength and tensile strain in natural hybrid fiber composites.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid composites showed 40% higher mechanical properties than individual fiber composites. Moudood et al [26] studied the mechanical properties of flax fiber reinforced composites at different relative humidifies: experimental, geometric, and displacement potential function approaches. The experimental results indicated that improved tensile strength and tensile strain in natural hybrid fiber composites.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, regarding flax fibers with specific mechanical strength even comparable with those of conventional ones (e.g., glass fibers), some interesting experimental results have already been collected. [ 26 ] Bozaci et al [ 27 ] studied the plasma modification of flax fibers to improve their interfacial adhesion in polymer composites based on high‐density polyethylene and unsaturated polyester. In this regard, the effect of plasma processes by atmospheric air and argon as the power varies, with the same exposure time, on the morphological, structural, and mechanical properties of the fibers and related composites were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…These properties increased up to 40% and then decreased. Moudood et al [43] studied the mechanical properties of flax fibers under various environmental conditions. The mechanical properties that were measured experimentally agreed strongly with the statistical results.…”
Section: Introductionmentioning
confidence: 99%